2006
DOI: 10.1074/jbc.m600314200
|View full text |Cite
|
Sign up to set email alerts
|

Pir Proteins of Saccharomyces cerevisiae Are Attached to β-1,3-Glucan by a New Protein-Carbohydrate Linkage

Abstract: A family of covalently linked cell wall proteins of Saccharomyces cerevisiae, called Pir proteins, are characterized by up to 10 conserved repeating units. Ccw5/Pir4p contains only one complete repeating sequence and its deletion caused a release of the protein into the medium. Fungal cell walls are rigid albeit dynamic, complex structures, withstanding intracellular osmotic pressures of more than 10 bar (1). In Saccharomyces cerevisiae the cell wall amounts to about 20% of the total dry weight of the cell. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
163
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(177 citation statements)
references
References 28 publications
5
163
0
Order By: Relevance
“…It was reported previously that Scw4p is a protein non-covalently attached to glucan (Cappellaro et al, 1998), but even after extensive extraction of cell walls with hot SDS, a portion of the protein remained and could only be extracted from the walls by mild alkali. Such a result is surprising, since Scw4p does not contain the Pir-repetitive sequence shown to be an absolute requirement for incorporation of Pir proteins by an alkali-sensitive linkage (Ecker et al, 2006). However, this is in accordance with the recent findings of Yin et al (2005), who also identified Scw4p among alkaliextractable cell wall proteins, using tandem mass spectrometry of peptides released by proteolytic digestion of SDS-treated S. cerevisiae cell walls.…”
Section: Identification and Phenotype Of Mutants Lacking Alkali-extrasupporting
confidence: 67%
See 4 more Smart Citations
“…It was reported previously that Scw4p is a protein non-covalently attached to glucan (Cappellaro et al, 1998), but even after extensive extraction of cell walls with hot SDS, a portion of the protein remained and could only be extracted from the walls by mild alkali. Such a result is surprising, since Scw4p does not contain the Pir-repetitive sequence shown to be an absolute requirement for incorporation of Pir proteins by an alkali-sensitive linkage (Ecker et al, 2006). However, this is in accordance with the recent findings of Yin et al (2005), who also identified Scw4p among alkaliextractable cell wall proteins, using tandem mass spectrometry of peptides released by proteolytic digestion of SDS-treated S. cerevisiae cell walls.…”
Section: Identification and Phenotype Of Mutants Lacking Alkali-extrasupporting
confidence: 67%
“…Plasmids containing CCW5 with exchanged specific amino acids pCCW5-HA used in this work (CCW5 plasmid containing haemagglutinin epitope at the C-terminus) was prepared by PCR as already described by Ecker et al (2006), as well as pCCW5 plasmids containing CCW5 with exchanged specific amino acids [pCCW5-(Q69A)-HA, pCCW5- …”
Section: Overproduction Of Scw4pmentioning
confidence: 99%
See 3 more Smart Citations